Legal Implications of a Good Faith Land Buyer Based on a Binding Agreement for Sale and Purchase in Full Entered Into Bankruptcy Boedel - Rudi Indra Jaya; Habib Adjie (PT Publikasiku Academic Solution, 2024)
The results of this study show that the regulations used as the basis for the bankruptcy boedel on land purchased based on evidence in the form of a Sale and Purchase Binding Agreement (PPJB) in full entered by the receivership into the bankruptcy boedel section are generally based on Articles 1131, 1132 of the Civil Code and Article 21 of the Bankruptcy Law and PKPU. When examining point b of the formulation of the civil chamber law number 7 SEMA Number 4 of 2016 that the purchase of land in good faith which is only proven by PPJB is paid off and the land is under its control, then the ownership of the land is legally valid. Therefore, the determination of bankruptcy boedel by the curator must heed the element of justice for land buyers in good faith. The legal implication of the act of the curator deliberately inserting the land that was sold and purchased based on PPJB Paid into the bankruptcy boedel is that it can be canceled. The cancellation can be done through a lawsuit filed by the buyer as stipulated in Article 3 paragraph (1) of the Bankruptcy Law and PKPU. This is because the purchase of land and/or buildings purchased by buyers who have good intentions and have been physically controlled is legally valid, therefore the act of the curator entering the buyer's land previously purchased from the seller based on PPJB Lunas is a wrong legal act, because it has implications for harming buyers who have obtained the land by legal means